PROFIL USAHA MANISAN PALA â€œKOMO JAYAâ€ DI KELURAHAN LAWANGIRUNG KECAMATAN WENANG - Norman Powell Kumontoy; Jenny . Baroleh; Gene H. Kapantow; Celsius . Talumingan (Universitas Sam Ratulangi, 2013)
ABSTRACTNutmeg is one of the commodities that have high economic value. The nutmeg most can be used as candied fruit which is generally done by the home industry. The object of this research is to know the business profile of candied nutmeg â€œKomo Jayaâ€ in terms of raw materials, capital, labor, production, production costs of business management, technology, and the amount of profit earned. The study was conducted during the months of September to November 2012, located in the Village District Lawangirung Wenang. The data obtained owners candied nutmeg through interviews by the researcher and was analysed in form of descriptions and figures and tables. The result of research showed that, this business is a home industry that has been hereditary or a family inheritance. The whole working processes of the production of candied nutmeg done by the industry owners. Candied nutmeg also has obtained a license from the Ministry of Health to be consumed. Owners of industrial candied nutmeg